Necesidad de reformar al Código del Trabajo, codificando una institución jurídica, las gratificaciones a las que se refiere el parágrafo 3ro. de las remuneraciones adicionales, para los operarios y aprendices de artesanos - Vera Ibarra, María Belén (2015)
In our Code of the Work it is established and normed the artisan activity, in a same way is regulated the contracts that can takes place so much with a contractor that is the person that takes charge the execution from a certain work to an artisan, as well as the contracts of operatives and apprentices with the artisan that you/they are fundamentally labor contracts. Of what we can determine that a labor relationship is born that brings some consequences or obligations for each one of the contractual parts, for example, the worker has the obligation of lending his licit and personal services, and the employer the obligation of paying the remuneration accorded in the contract that cannot be inferior to the basic one established, he also has the obligation of paying the additional remunerations settled down in the Code of the Work. The additional remunerations to those that we refer are however the thirteenth and fourteenth remunerations that are of obligatory payment from the employer to the worker, in the article 115 of the Code of the Work, it is established the exclusion to the payment of these additional remunerations to the apprentices and artisan's operatives who for their condition of workers, and according to the constitutional principles that establish the protection of the worthy wage for the workers and that to equal work it corresponds him same remuneration, they should not be discriminated against by the same Law this way. According to these constitutional dispositions that aid the work, the worthy wage that covers the worker's necessities and those of their family, it is necessary and indispensable to carry out a legal reformation to the Code of the Work, pretending to include in the right to perceive the additional remunerations to the apprentices and artisan's operatives. The reformation is guided to that the artisans recognize the work executed by the operatives and apprentices remunerating them in a worthy way that its wage covers the basic necessities of these workers, since they have right equal that the other workers conform it determines the Constitution: the equality of rights and opportunities for all the Ecuadorian citizens